Digital Techniques for Documenting and Preserving Cultural Heritage - Bentkowska-Kafel, Anna; MacDonald, Lindsay; Bentkowska-Kafel, Anna; MacDonald, Lindsay (Arc Humanities Press, 2018)
This book presents interdisciplinary approaches to the examination and documentation of material cultural heritage, using non-invasive spatial and spectral optical technologies.
English
Keywords: Museology & heritage studies; Conservation, restoration & care of artworks; Archaeological science, methodology & techniques; Archiving, preservation & digitisation; Cultural heritage; Science; Documentation; Digital Humanities